Garlic (Allium sativum) polysaccharides ameliorates hepatic injury and fat accumulation in mice with metabolic associated fatty liver disease (MAFLD). (December 2022) - Liu, Jie; Yu, Wangning; Wang, Chenghai; Li, Sha; Zhang, Wei
Graphical abstract: Highlights: GP treatment has a beneficial effect on MAFLD induced by the MCD diet. MCD diet up-regulates the expression of Cd36 through NF kappa-B signaling pathway. GP proliferates Faecalibaculum in the intestinal microbial fermentation stage. GP has a significant effect on bile acid metabolic pathways. Abstract: Background: Previous studies have shown that garlic polysaccharides (GP) can protect the liver, but its mechanism is unclear. We are interested in whether it can alleviate metabolic associated fatty liver disease (MAFLD). Scope and approach: The MAFLD mice model was established by Methionine-choline deficiency (MCD) diet induction. The experimental group was established by feeding with GP by gavage. The liver protective effect of GP and its possible mechanism were studied by means of microscopic examination, biochemical analysis, quantitative analysis of mRNA, metabolome, and gut microbiota analysis. Key Findings and Conclusion: GP treatment had a beneficial effect on hepatic injury and fat accumulation. Serum metabolome and gut microbiota analysis results indicate that GP had a significant proliferative effect on Faecalibaculum . In addition, GP also had a substantial impact on bile acid metabolic pathways. These findings provide new insights into the pathogenesis of MAFLD and provide further evidence for the potential use of GP as an alternative functional ingredient.